The Cyclic AMP Receptor Protein, Crp, Is Required for the Decolorization of Acid Yellow 36 in Shewanella putrefaciens CN32 - Liu, Weijie; Chen, Ying; Zhou, Xuge; Liu, Jiawen; Zhu, Jingrong; Wang, Shiwei; Liu, Cong; Sun, Di (Frontiers in Microbiology, 2020)
Shewanella shows good application potentials in the decolorization and detoxification of azo dye wastewater. However, the molecular mechanism of decolorization is still lacking. In this study, it was found that Shewanella putrefaciens CN32 exhibited good decolorization ability to various azo dyes and a global regulatory protein Crp was identified to be required for the decolorization of acid yellow 36 (AY) by constructing transposon mutant library. Then, the molecular mechanism of AY decolorization regulated by Crp was further investigated. The RT-qPCR and EMSA results showed that Crp was able to directly bind to the promoter region of cymA gene and promote its expression. Riboflavin acted as an electron shuttle could accelerate AY decolorization efficiency of S. putrefaciens CN32 wild-type (WT), but did not show promoting effect to Δcrp mutant and ΔcymA mutant, further confirming that Crp promotes the decolorization through regulating electron transport chains. Moreover, the mutant with cymA overexpression could slightly enhance the AY decolorization efficiency compared with the WT strain. In addition, it was found that MtrA, MtrB and MtrC partially contribute to the electron transfer from CymA to dye molecules and other main electron transport chains need to be identified in future experiments. This study revealed that the molecular mechanism of a global regulator Crp regulating the decolorization of azo dye, which is helpful to understand the relationship between the decolorization and other metabolic processes in S. putrefaciens CN32.